Rancang Bangun Web Portal Berita Sebagai Sumber Informasi Berita Tentang Pertanian - Yudo Devianto; Saruni Dwiasnati (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
In the era of technology 4.0, the development of science and technology is very rapid at this time, especially internet network technology. Almost all parts of the world use this technology to find and disseminate information. Likewise in Indonesia, most of its citizens use internet technology to find and disseminate information. Based on the results of the 2018 APJII survey, internet users still have the highest percentage on the islands of Java and Sumatra. We intend to create a news portal, but this news portal will inform only news about agriculture. What is meant by agriculture here is the use of biological resources by humans to produce food, industrial raw materials, or energy sources. This news portal will be devoted to informing agricultural products and products produced by villages, so that they can be widely known and it is hoped that being widely known will improve the economy of the village community. This is in line with law number 6 of 2014 "Concerning Villages", article 86 "Information Systems for Village Development and Rural Area Development". This E-News news portal application is designed to inform news related to the agricultural sector. With the news information from the E-News news portal, the general public can find out about the development of the agricultural sector, and especially farmers get additional information related to the agricultural sector.